What makes a family - Faulkner, Colleen (Kensington Books, 2017)
Nestled in the Chesapeake Bay, Brodie Island is charming, remote, and slow to change. For three hundred years, Abby Brodie<U+2019>s farming family has prospered there. Now, years after leaving to make her way on her own terms, Abby is coming home to see her ailing grandmother, with her teenage daughter and a wealth of memories in tow. Yet as family members gather at the old farmhouse, Abby realizes this visit offers more than a chance to say goodbye. After decades of feeling she was a disappointment as a daughter, Abby is beginning to see that her mother, too, has struggled to feel a sense of belonging within the Brodie family. Celeste, Abby<U+2019>s self-centered sister, is far from the successful actress she pretends to be, and needs help that only Abby and their half-brother, Joseph, can give. But most surprising of all is the secret that Grandmother Brodie has been carrying<U+2014>one that will make each woman question her identity and the sacrifices she<U+2019>s willing to make to gain acceptance.